Numerical study on all-optical modulation characteristics of quantum cascade lasers - Wei, Biao; Zhou, Haijun; Li, Guangxiang; Tang, Bin (Beilstein Journal of Nanotechnology, 2022)
To explain the phenomenon of all-optical modulation of quantum cascade laser (QCL), and explore the physics in QCL’s gain medium which consists of multiple of dielectric nanostructures with high refractive index under light injection, we modified the 1½-period model to calculate values of electron population and lifetime in each subband which is separated by the nanostructures, optical gain, current and number of photons in the cavity of a mid-infrared QCL modulated with near-infrared optical injection. The results were consistent with an experiment, where the injected light increases the electron population and lifetime, but does not affect the optical gain obviously. Our study can be helpful for optimizing its use and dielectric nanostructure design.
Keywords: all-optical modulation; dielectric nanostructures; high refractive index materials; numerical study; quantum cascade lasers